Implementation of Restorative Justice in Traffic Accident Cases in Sukabumi City Viewed from Reintegrative Shaming Theory - Rozak, Abdur; Nurhadiyanto, Lucky (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
This study aims to describe the implementation of restorative justice approach in handling traffic accident cases in Sukabumi City, focusing on the theory of reintegrative shaming. Restorative justice offers a different alternative to conflict resolution, prioritizing the repair of relationships between perpetrators, victims and communities. In the context of traffic accidents, this approach highlights a process of learning and accountability that can result in improved behavior and healing for all parties involved. This research will use a qualitative method with data collection techniques through interviews with relevant parties, observation, and literature study. The data collected will be analyzed using the reintegrative shaming theory approach to understand the effectiveness and impact of the application of restorative justice in traffic accident cases in Sukabumi City. The results of this research are expected to provide deeper insights into how this approach can be applied effectively in the context of criminal law and restorative justice, making policies that are unified and provide recommendations for improving a more just and rehabilitative law enforcement system in handling traffic accident cases.